Republika Turcji na arenie międzynarodowej - Bobin, Ewa (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The Republic of Turkey is a very special country, in terms of political, geographi-cal, social and cultural. The author presents the actual situation in Turkey and its internal and foreign policies. In this article is submitted the process and the condi-tion of the foreign relations of Turkey with its neighbors (the eight countries which is bordered by) and with Russia and the United States of America. Moreover, it is described the membership of Turkey in the international organizations, including the European Union. Finding a place for Turkey in the arena of international poli-tics is a very difficult task because it is the country situated “between the West and the East of the world”. This is the reason why it is worth to take considerations in this subjects
Keywords: Turcja; stosunki międzynarodowe; Unia Europejska